A high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity and a preparation method thereof
By optimizing the composition and content of high specific gravity tungsten alloy, it precipitates L12 phase in the gamma solid solution phase, solving the problem that existing tungsten alloys are difficult to achieve high density, high strength plasticity and good thermal insulation shear performance at the same time, and realizing tungsten alloys multiple performance improvements.
Patent Information
- Application Number
- CN202310028881.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-09
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-01-09
AI Technical Summary
It is difficult for existing high specific gravity tungsten alloys to achieve the combination of high density, high strength plasticity and good thermal insulation shear performance at the same time.
By selecting the appropriate composition of high specific gravity tungsten alloy and optimizing the content of each component, L12 phase with certain stability and certain content is precipitated in the gamma solid solution phase, thereby ensuring that the tungsten alloy has high density, ultra-high strength, high plasticity and Excellent adiabatic shear sensitivity.
It realizes the high density, ultra-high strength, high plasticity and excellent thermal insulation shear sensitivity of tungsten alloys. It has simple preparation technology, easy to produce on a large scale, and has good application prospects.
Smart Images

Figure CN116240437B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-density tungsten alloy with high adiabatic shear sensitivity and high-strength plasticity and a preparation method thereof, belonging to the technical field of high-density tungsten alloys. Background Art
[0002] High-density tungsten alloys usually refer to tungsten phases with BCC structure and γ solid solution phases with FCC structure, and the density is as high as 16.5-19.0g / cm 3 The density of high-density tungsten alloys with different compositions is also different. High-density tungsten alloys play a huge role in the weapons industry, especially in the core rod material of armor-piercing bullets, due to their high density, high strength and environmentally friendly properties.
[0003] However, traditional tungsten alloys represented by W-Ni-Fe alloys are prone to form "mushroom"-shaped blunted warheads during kinetic penetration, resulting in energy loss and limiting their penetration capabilities. In order to improve the adiabatic shear sensitivity of high-density tungsten alloys, large deformation and grain refinement are usually used, but the process is relatively complicated and there is limited room for improvement. For example: Chinese patent CN115007645A (a method for improving the adiabatic shear sensitivity of pure tungsten metal through crystal texture design, published on September 6, 2022), this patent changes the initial crystal orientation of tungsten metal through large deformation, thereby improving the adiabatic shear sensitivity of pure tungsten metal, but this method has high requirements on material plasticity and is difficult to produce.
[0004] The "self-sharpening" effect is currently a common means to improve the penetration ability of high-density tungsten alloys. For example, Chinese patent CN111283212A (a delamination self-sharpening structure tungsten alloy material and its preparation method and application, published on 2020-06-16) rolls and deforms the plate-type tungsten-nickel-iron alloy to obtain a deformed tungsten-nickel-iron alloy, and prepares a delamination self-sharpening structure tungsten alloy material, but does not obtain the self-sharpening effect from the material itself, and increases the processing cost to a certain extent. Summary of the invention
[0005] In view of the problem that it is difficult for current high-density tungsten alloys to achieve an organic combination of high density, high strength plasticity and good adiabatic shear performance, the present invention provides a high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity and a preparation method thereof. By selecting the components of the high-density tungsten alloy and optimizing the content of each component, an L12 phase with a certain stability and a certain content is precipitated in the γ solid solution phase, thereby ensuring that the tungsten alloy has high density, ultra-high strength, high plasticity and excellent adiabatic shear sensitivity. The preparation process of the tungsten alloy is simple, easy to operate, meets the needs of large-scale production, and has good application prospects in the field of weapons industry.
[0006] The objectives of the present invention are achieved through the following technical solutions.
[0007] A high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity is a tungsten alloy composed of W, Co, Al, M and N according to the mass percentage of a:b:c:d:e, M is at least one of Ni, Fe, V, Cr, Ta and Nb, N is at least one of Y, V, Mo, Mn, Hf and Ti, 90%≤a≤95%, 1%≤b≤8%, 0.5%≤c≤4.5%, 0≤d≤3%, 0≤e≤3%, and d+e<b, a+b+c+d+e=100%. The microstructure of the tungsten alloy includes W phase, γ solid solution phase and L12 phase, and the density is 17.5-18.4g / cm 3 The quasi-static compression strength is above 1900MPa, the quasi-static compression elongation is above 20%, and after dynamic compression, it exhibits adiabatic shear failure.
[0008] Preferably, the M element is at least one of Ni, Fe, and Ta, and the N element is one or both of Hf and Ti.
[0009] Preferably, 90%≤a≤95%, 3%≤b≤7%, 0.5%≤c≤3%, 0≤d≤2.5%, 0≤e≤2.5%, and d+e<b, a+b+c+d+e=100%.
[0010] The preparation method of high-density tungsten alloy with high adiabatic shear sensitivity and high strength and plasticity specifically comprises the following steps:
[0011] (1) uniformly mixing the single substance powders corresponding to each element, or uniformly mixing the W single substance powder and the CoAlMN alloy powder to obtain a mixed powder;
[0012] (2) liquid-phase sintering the mixed powder to obtain a sintered body;
[0013] (3) The sintered body is subjected to annealing or hot isostatic pressing to obtain the tungsten alloy.
[0014] In step (1), after weighing each raw material powder, uniformly mix them at a speed of 30 to 600 r / min for 4 to 24 hours under an inert gas protective atmosphere, and then place them in a vacuum drying oven at 100 to 180° C. for vacuum drying for 2 to 8 hours to obtain a mixed powder.
[0015] In step (2), the sintered body can be prepared by a conventional liquid phase sintering process or a laser instantaneous liquid phase sintering process. The conventional liquid phase sintering process uses a box-type high temperature sintering furnace, firstly heating the temperature to 700-1000°C at a heating rate of 5-20°C / min and keeping the temperature for 60-120min, then heating the temperature to 1300-1700°C at a heating rate of 2-20°C / min and keeping the temperature for 0-120h, and then cooling to obtain a sintered body. The laser instantaneous liquid phase sintering process uses laser as the heat source, only melts the matrix in a tiny molten pool, while keeping most of the tungsten particles in the molten pool unmelted, to achieve ultra-short liquid phase sintering. This technology can better control the growth of tungsten particles and avoid segregation of tungsten alloy components. The specific process parameters are as follows: laser power 800~2000W, scanning rate 300~1500mm / min, powder feeding rate 15~45g / min, scanning spacing 1.0~3.0mm, and elevation 0.1~0.5mm.
[0016] In step (3), the annealing temperature of the annealing treatment is 500-1100° C. and the annealing time is 2-24 h; the temperature of the hot isostatic pressing treatment is 800-1500° C., the pressure is 80-230 MPa and the time is 2-24 h.
[0017] Beneficial effects:
[0018] (1) The tungsten alloy described in the present invention introduces the W element into the matrix, and by adjusting the element ratio, the W element combines with other elements in the matrix phase to generate the L12 type precipitation phase of Co3 (Al, W), thereby ensuring the high density and high strength of the tungsten alloy while avoiding alloy embrittlement.
[0019] (2) The L12 phase is introduced into the tungsten alloy of the present invention. The high-temperature decomposition property of the L12 phase is utilized to make the tungsten alloy have high adiabatic shear sensitivity and "shear self-sharpening" capability.
[0020] (3) The tungsten alloy of the present invention can regulate the content of intermetallic compounds in the alloy by adjusting the type and content of M and N elements, thereby making better regulation on the mechanical properties, density and adiabatic shear sensitivity of the alloy. When M and N elements are not added, the precipitated phase in the tungsten alloy is less and the strength is lower; when too much M and N elements are added, the type and content of intermetallic compounds in the tungsten alloy change, which is not conducive to the plasticity and adiabatic shear sensitivity of the tungsten alloy.
[0021] (4) In the preparation process of the tungsten alloy described in the present invention, two sintering processes, namely traditional liquid phase sintering and laser instantaneous liquid phase sintering, are used to effectively achieve the coordination between W particle size control and WW connectivity control, thereby ensuring various performance indicators of the tungsten alloy; and the content and morphology of the precipitated phase can be effectively regulated through subsequent heat treatment to ensure the performance of the alloy.
[0022] (5) The tungsten alloy of the present invention has high density, ultra-high strength, high plasticity and excellent adiabatic shear sensitivity, and has a simple preparation process, high production efficiency, and is easy for industrial production, and has good application prospects in the field of weapons industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the X-ray diffraction (XRD) pattern of the 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy prepared by traditional liquid phase sintering technology in Example 1.
[0024] Figure 2 This is a scanning electron microscope (SEM) image of the 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy prepared by traditional liquid phase sintering technology in Example 1.
[0025] Figure 3 for Figure 2 A local magnified scanning electron microscope image of the L12 phase.
[0026] Figure 4 This is the quasi-static compressive stress-strain curve of the 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy prepared by traditional liquid phase sintering technology in Example 1.
[0027] Figure 5 This is the X-ray diffraction pattern of the 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy prepared by laser transient liquid phase sintering technology in Example 4.
[0028] Figure 6 This is a scanning electron microscope image of the 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy prepared by laser transient liquid phase sintering technology in Example 4.
[0029] Figure 7 for Figure 6 A local magnified scanning electron microscope image of the L12 phase.
[0030] Figure 8 This is the quasi-static compressive stress-strain curve of the 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy prepared by laser transient liquid phase sintering technology in Example 4.
[0031] Fig. 9 This is the dynamic compression true stress-strain curve of the 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy prepared by laser transient liquid phase sintering technology in Example 4. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.
[0033] Performance testing and structural characterization:
[0034] (1) Density determination: According to the standard GB-5365-2005, the density of tungsten alloy was tested using a DT-100 precision balance, and the sample size was Φ4mm×4mm;
[0035] (2) Phase analysis: Phase analysis was performed using a D8 advance X-ray diffractometer from Bruker AXS, Germany. The operating voltage and current were 40 kV and 40 mA, respectively. The X-ray source was CuKα (λ = 0.1542 nm). The scanning speed was 0.2 sec / step, the scanning step was 0.02° / step, and the scanning range was 20° to 100°.
[0036] (3) Morphology observation: The microscopic morphology was characterized by using a REGULUS 8230 cold field emission scanning electron microscope (SEM) from Hitachi, Japan, and backscattered electron imaging with an operating voltage of 10 to 25 kV.
[0037] (4) Dynamic compression test: According to the standard GJB-5365-2005, the room temperature axial dynamic compression mechanical properties of tungsten alloy were tested using a split Hopkins pressure bar (SHPB). The sample size was Φ4×4mm and the strain rate was ~10 3 s -1 ;
[0038] (5) Quasi-static compression test: According to the standard GB / T7314-2017, the room temperature axial quasi-static compression mechanical properties of tungsten alloy were tested using INSTRON5582 equipment. The sample size was Φ4×6mm and the strain rate was ~10 -3 s -1 .
[0039] Example 1
[0040] The specific steps of preparing 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy by traditional liquid phase sintering process are as follows:
[0041] (1) After the pure metal blocks of Co, Al, Ta and Ti with a purity of not less than 99.7% are polished, cleaned and dried, a mixed raw material with a total mass of 2000±0.01 g is weighed according to the mass ratio of Co:Al:Ta:Ti=40:5:3:2; the weighed mixed raw materials are placed in a water-cooled copper crucible of a vacuum gas atomization powder making furnace in the order of their melting points from low to high, and then the furnace is evacuated until the vacuum degree in the furnace reaches 3×10-3 After the alloy is completely melted into alloy liquid, argon is used as an atomizing medium to atomize the alloy liquid at a heating power of 160 kW and an atomizing pressure of 4 MPa, and then a Co-Al-Ta-Ti pre-alloyed powder with a particle size of 38 to 150 μm is obtained through a vacuum screening device;
[0042] (2) Spherical W powder with a particle size range of 15 to 25 μm and the Co-Al-Ta-Ti pre-alloyed powder prepared in step (1) are weighed at a mass ratio of 95:5 to obtain a mixed powder with a total mass of 1000±0.01 g, and the mixed powder is placed in a clean and blown-dried V-type powder mixer, mixed at a speed of 300 r / min for 24 h, and then placed in a vacuum drying oven at 130° C. for vacuum drying for 4 h to obtain a uniformly mixed and dry mixed powder;
[0043] (3) The mixed powder obtained in step (2) is placed in a cold isostatic pressing mold of Φ20 mm×180 mm and sealed, and then placed in a cold isostatic press, pressurized to 150 MPa and maintained at the pressure for 25 minutes, taken out, cleaned, demolded to obtain a pressed green body; the pressed green body is placed in a crucible covered with alumina particles and placed in a box-type high-temperature sintering furnace, first heated to 900°C at a heating rate of 20°C / min and kept warm for 120 minutes, then heated to 1600°C at a heating rate of 10°C / min and kept warm for 12 hours, and then cooled to obtain a sintered body;
[0044] (4) The sintered body was hot isostatically pressed at 900°C and 120 MPa for 10 h to obtain a 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy.
[0045] The test shows that the density of the prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy is 17.6g / cm 3 .
[0046] The prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy was analyzed for phase. Figure 1 It can be seen from the XRD spectrum that the tungsten alloy is mainly composed of W phase and γ solid solution phase, and also contains a small amount of L12 phase and Co7W6 phase.
[0047] The microstructure of the prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy was observed. Figure 2 The SEM image shows that the light-colored W phase is evenly distributed in the dark-colored γ solid solution phase, forming a large number of two-phase interfaces, and there are also nano-sized L12 phases in the γ solid solution phase (such as Figure 3As shown in Figure 2). The addition of Ta and Ti elements can greatly increase the content of L12 phase, so that more L12 phase can participate in improving the adiabatic shear sensitivity, thereby improving the adiabatic shear sensitivity of tungsten alloy; at the same time, the addition of Ta and Ti elements also plays a good role in solid solution strengthening, improving the mechanical properties of tungsten alloy. In addition, the high content of W leads to the generation of Co7W6 phase in tungsten alloy, which can further improve the adiabatic shear sensitivity, but sacrifices the plasticity of tungsten alloy to a certain extent.
[0048] The prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy was subjected to quasi-static compression test. Figure 4 The test results show that the compressive strength of the tungsten alloy is 2200MPa and the fracture deformation is 34%.
[0049] A dynamic compression test was carried out on the prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy, and the tungsten alloy showed adiabatic shear failure.
[0050] Example 2
[0051] The specific steps of preparing 90W-8Co-1.5Al-0.3Ta-0.2Ti tungsten alloy by traditional liquid phase sintering process are as follows:
[0052] (1) Weigh 1000±0.01 g of mixed powder of W, Co, Al, Ta and Ti with a purity of not less than 99.99% in a mass ratio of 90:8:1.5:0.3:0.2, pour the mixed powder into a clean and blown-dried V-type powder mixer, mix at a speed of 300 r / min for 24 h, and then place it in a vacuum drying oven at 130° C. for 4 h to obtain a uniformly mixed and dry mixed powder; wherein the particle size of the W single substance powder is not greater than 15 μm, and the particle size of the other metal single substance powders is not greater than 38 μm;
[0053] (2) The mixed powder obtained in step (1) is placed in a cold isostatic pressing mold of Φ20 mm×180 mm and sealed, and then placed in a cold isostatic press, pressurized to 170 MPa and maintained for 75 min, taken out, cleaned, demolded to obtain a pressed green body; the pressed green body is placed in a crucible covered with alumina particles and placed in a box-type high-temperature sintering furnace, first heated to 900°C at a heating rate of 20°C / min and kept warm for 120 min, then heated to 1600°C at a heating rate of 10°C / min and kept warm for 24 h, and then cooled to obtain a sintered body;
[0054] (3) The sintered body was hot isostatically pressed for 10 h at 1000 °C and 120 MPa, 90W-8Co-1.5Al-0.3Ta-0.2Ti tungsten alloy.
[0055] The test shows that the density of the prepared 90W-8Co-1.5Al-0.3Ta-0.2Ti tungsten alloy is 17.1g / cm 3 .
[0056] The microstructure of the prepared 90W-8Co-1.5Al-0.3Ta-0.2Ti tungsten alloy was observed, and it was found that the tungsten alloy was mainly composed of W phase and γ solid solution phase, and micron-sized L12 phase was precipitated in the γ solid solution phase.
[0057] A dynamic compression test was carried out on the prepared 90W-8Co-1.5Al-0.3Ta-0.2Ti tungsten alloy, and the tungsten alloy showed adiabatic shear failure.
[0058] Example 3
[0059] The specific steps of preparing 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy by traditional liquid phase sintering process are as follows:
[0060] (1) Weigh 1000±0.01 g of mixed powder of W, Co, Al, Ta and Ti with a purity of not less than 99.99% in a mass ratio of 95:4:0.5:0.3:0.2, pour the mixed powder into a clean and blown-dried V-type powder mixer, mix at a speed of 300 r / min for 24 h, and then place it in a vacuum drying oven at 130° C. for 4 h to obtain a uniformly mixed and dry mixed powder; wherein the particle size of the W single substance powder is not greater than 15 μm, and the particle size of the other metal single substance powders is not greater than 38 μm;
[0061] (2) The mixed powder obtained in step (1) is placed in a cold isostatic pressing mold of Φ20 mm×180 mm and sealed, and then placed in a cold isostatic press, pressurized to 200 MPa and maintained for 75 min, taken out, cleaned, demolded to obtain a pressed green body; the pressed green body is placed in a crucible covered with alumina particles and placed in a box-type high-temperature sintering furnace, first heated to 900°C at a heating rate of 20°C / min and kept warm for 120 min, then heated to 1600°C at a heating rate of 10°C / min and kept warm for 24 h, and then cooled to obtain a sintered body;
[0062] (3) The sintered body was subjected to hot isostatic pressing at 1000°C and 120 MPa for 10 h to obtain 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy.
[0063] The test shows that the density of the prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy is 17.7g / cm 3 .
[0064] The microstructure of the prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy was observed, and it was found that the tungsten alloy was mainly composed of W phase and γ solid solution phase, and micron-sized L12 phase was precipitated in the γ solid solution phase.
[0065] A dynamic compression test was carried out on the prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy, and the tungsten alloy showed adiabatic shear failure.
[0066] Example 4
[0067] The specific steps of preparing 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy by laser transient liquid phase sintering process are as follows:
[0068] (1) After the pure metal blocks of Co, Al, Ta and Ti with a purity of not less than 99.7% are polished, cleaned and dried, a mixed raw material with a total mass of 2000±0.01 g is weighed according to the mass ratio of Co:Al:Ta:Ti=40:5:3:2; the weighed mixed raw materials are placed in a water-cooled copper crucible of a vacuum gas atomization powder making furnace in the order of their melting points from low to high, and then the furnace is evacuated until the vacuum degree in the furnace reaches 3×10 -3 After the alloy is completely melted into alloy liquid, argon is used as an atomizing medium to atomize the alloy liquid at a heating power of 160 kW and an atomizing pressure of 4 MPa, and then a Co-Al-Ta-Ti pre-alloyed powder with a particle size of 38 to 150 μm is obtained through a vacuum screening device;
[0069] (2) Spherical W powder with a particle size range of 15 to 25 μm and the Co-Al-Ta-Ti pre-alloyed powder prepared in step (1) are weighed at a mass ratio of 95:5 to obtain a mixed powder with a total mass of 1000±0.01 g, and the mixed powder is placed in a clean and blown-dried V-type powder mixer, mixed at a speed of 300 r / min for 24 h, and then placed in a vacuum drying oven at 130° C. for vacuum drying for 4 h to obtain a uniformly mixed and dry mixed powder;
[0070] (3) The mixed powder obtained in step (2) was loaded into a powder tank of a laser transient liquid phase sintering device, and the laser power was set to 1800 W, the scanning rate was 900 mm / min, the powder feeding rate was 28 g / min, the scanning spacing was 2.0 mm, and the elevation was 0.35 mm, and a sintered body was prepared using the laser as a heat source;
[0071] (4) The sintered body was annealed at 700°C for 10 h to obtain 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy.
[0072] The test shows that the density of the prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy is 17.4g / cm 3 .
[0073] The prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy was analyzed for phase. Figure 5 It can be seen from the XRD spectrum that the tungsten alloy is mainly composed of W phase and γ solid solution phase, and also contains a small amount of L12 phase.
[0074] The microstructure of the prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy was observed. Figure 6 From the SEM images, we can see that the light-colored W phase is evenly distributed in the dark-colored γ solid solution phase, forming a large number of two-phase interfaces. There are 100-nanometer-sized L12 phases in the tungsten alloy γ solid solution (such as Figure 7 shown).
[0075] The prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy was subjected to quasi-static compression test. Figure 8 The test results show that the compressive strength of the tungsten alloy is 2400MPa and the fracture deformation is 25%.
[0076] The prepared 95W-4Co-0.5Al-0.3Ta-0.2Ti tungsten alloy was subjected to dynamic compression test. Fig. 9 The test results show that the dynamic compression strength of the tungsten alloy is 2750MPa and the fracture strain is 20%. After the dynamic compression test, it shows adiabatic shear failure.
[0077] Example 5
[0078] The specific steps of preparing 93W-3.5Co-3Hf-0.5Al tungsten alloy by traditional liquid phase sintering process are as follows:
[0079] (1) After the pure metal blocks of Co, Hf and Al with a purity of not less than 99.7% are polished, cleaned and dried, a mixed raw material with a total mass of 2000±0.01g is weighed according to the mass ratio of Co:Hf:Al=35:30:5; the weighed mixed raw materials are placed in a water-cooled copper crucible of a vacuum gas atomization powder making furnace in the order of their melting points from low to high, and then the furnace is evacuated until the vacuum degree in the furnace reaches 3×10 -3 After the temperature reaches 10000 Pa, high-purity argon is filled as a protective gas, and then alloying smelting is performed. After the alloy is completely melted into alloy liquid, argon is used as an atomizing medium, and the alloy liquid is atomized and powdered at a heating power of 150kW and an atomizing gas pressure of 4MPa, and then a Co-Hf-Al pre-alloyed powder with a particle size of ≤38μm is obtained through a vacuum screening device;
[0080] (2) Spherical W powder with a particle size of no more than 15 μm and the Co—Hf—Al pre-alloyed powder prepared in step (1) were weighed at a mass ratio of 93:7 to obtain a mixed powder with a total mass of 1000±0.01 g, and the mixed powder was placed in a clean and blown-dried V-type powder mixer, mixed at a speed of 300 r / min for 24 h, and then placed in a vacuum drying oven at 130° C. for vacuum drying for 4 h to obtain a uniformly mixed and dry mixed powder;
[0081] (3) The mixed powder obtained in step (2) is placed in a cold isostatic pressing mold of Φ20 mm×180 mm and sealed, and then placed in a cold isostatic press, pressurized to 150 MPa and maintained at a pressure of 75 min, taken out, cleaned, demolded to obtain a green compact; the green compact is placed in a crucible covered with alumina particles and placed in a box-type high-temperature sintering furnace, first heated to 850°C at a heating rate of 20°C / min and kept warm for 120 min, then heated to 1500°C at a heating rate of 10°C / min and kept warm for 16 h, and then cooled to obtain a sintered body;
[0082] (4) The sintered body was subjected to hot isostatic pressing at 900°C and 120 MPa for 10 h to obtain 93W-3.5Co-3Hf-0.5Al tungsten alloy.
[0083] The test shows that the density of the prepared 93W-3.5Co-3Hf-0.5Al tungsten alloy is 17.5g / cm 3 .
[0084] The microscopic morphology of the prepared 93W-3.5Co-3Hf-0.5Al tungsten alloy was observed, and it was found that the tungsten alloy was mainly composed of W phase and γ solid solution phase, and a small amount of L12 phase precipitated in the γ solid solution. The addition of Hf element effectively increased the L12 phase through alloying, and the addition of Hf element significantly improved the adiabatic shear sensitivity of the tungsten alloy.
[0085] The prepared 93W-3.5Co-3Hf-0.5Al tungsten alloy was subjected to a dynamic compression test, and the tungsten alloy exhibited adiabatic shear failure.
[0086] Example 6
[0087] The specific steps of preparing 93W-3.5Co-3Fe-0.5Al tungsten alloy by traditional liquid phase sintering process are as follows:
[0088] (1) After the pure metal blocks of Co, Fe and Al with a purity of not less than 99.7% are polished, cleaned and dried, a mixed raw material with a total mass of 2000±0.01g is weighed according to the mass ratio of Co:Fe:Al=35:30:5; the weighed mixed raw materials are placed in a water-cooled copper crucible of a vacuum gas atomization powder making furnace in the order of their melting points from low to high, and then the furnace is evacuated until the vacuum degree in the furnace reaches 3×10 -3 After the temperature reaches 10000 Pa, high-purity argon is filled as a protective gas, and then alloying smelting is performed. After the alloy is completely melted into alloy liquid, argon is used as an atomizing medium, and the alloy liquid is atomized and powdered at a heating power of 150kW and an atomizing gas pressure of 4MPa, and then a Co-Fe-Al pre-alloyed powder with a particle size of ≤38μm is obtained through a vacuum screening device;
[0089] (2) spherical W powder with a particle size of no more than 15 μm and the Co—Fe—Al pre-alloyed powder prepared in step (1) were weighed at a mass ratio of 93:7 to obtain a mixed powder with a total mass of 1000±0.01 g, and the mixed powder was placed in a clean and blown-dried V-type powder mixer, mixed at a speed of 300 r / min for 24 h, and then placed in a vacuum drying oven at 130° C. for vacuum drying for 4 h to obtain a uniformly mixed and dry mixed powder;
[0090] (3) The mixed powder obtained in step (2) is placed in a Φ20 mm × 180 mm cold isostatic pressing mold and sealed tightly, and then placed in a cold isostatic press, pressurized to 100 MPa and maintained at a pressure of 120 min, taken out, cleaned, demolded to obtain a green compact; the green compact is placed in a crucible covered with alumina particles and placed in a box-type high-temperature sintering furnace, first heated to 850° C. at a heating rate of 30° C. / min and kept warm for 120 min, then heated to 1500° C. at a heating rate of 10° C. / min and kept warm for 16 h, and then cooled to obtain a sintered body;
[0091] (4) The sintered body was hot isostatically pressed at 900°C and 120 MPa for 10 h to obtain 93W-3.5Co-3Fe-0.5Al tungsten alloy.
[0092] The test shows that the density of the prepared 93W-3.5Co-3Fe-0.5Al tungsten alloy is 17.5g / cm 3 .
[0093] The microstructure of the prepared 93W-3.5Co-3Fe-0.5Al tungsten alloy was observed, and it was found that the tungsten alloy was mainly composed of W phase and γ solid solution phase, and a small amount of L12 phase was washed out from the γ solid solution.
[0094] The prepared 93W-3.5Co-3Fe-0.5Al tungsten alloy was subjected to a dynamic compression test, and the tungsten alloy exhibited adiabatic shear failure.
[0095] Example 7
[0096] The specific steps of preparing 90W-8Co-2Al tungsten alloy by traditional liquid phase sintering process are as follows:
[0097] (1) After grinding, cleaning and drying pure metal blocks of Co and Al with a purity of not less than 99.7%, a mixed raw material with a total mass of 2000±0.01 g is weighed according to a mass ratio of Co:Al=8:2; the weighed mixed raw materials are placed in a water-cooled copper crucible of a vacuum gas atomization powder making furnace in the order of their melting points from low to high, and then the furnace is evacuated until the vacuum degree in the furnace reaches 3×10 -3 After the alloy is completely melted into alloy liquid, argon is used as an atomizing medium to atomize the alloy liquid at a heating power of 150kW and an atomizing pressure of 4MPa, and then a Co-Al pre-alloyed powder with a particle size of ≤38μm is obtained through vacuum screening equipment;
[0098] (2) spherical W powder with a particle size of no more than 15 μm and the Co-Al pre-alloyed powder prepared in step (1) are weighed in a mass ratio of 90:10 to obtain a mixed powder with a total mass of 1000±0.01 g, and the mixed powder is placed in a clean and blown-dried V-type powder mixer, mixed at a speed of 300 r / min for 24 h, and then placed in a vacuum drying oven at 130° C. for vacuum drying for 4 h to obtain a uniformly mixed and dry mixed powder;
[0099] (3) The mixed powder obtained in step (2) is placed in a Φ20 mm × 180 mm cold isostatic pressing mold and sealed tightly, and then placed in a cold isostatic press, pressurized to 100 MPa and maintained at a pressure of 120 min, taken out, cleaned, demolded to obtain a green compact; the green compact is placed in a crucible covered with alumina particles and placed in a box-type high-temperature sintering furnace, first heated to 850° C. at a heating rate of 30° C. / min and kept warm for 120 min, then heated to 1500° C. at a heating rate of 10° C. / min and kept warm for 16 h, and then cooled to obtain a sintered body;
[0100] (4) The sintered body was subjected to hot isostatic pressing at 900°C and 120 MPa for 10 h to obtain 90W-8Co-2Al tungsten alloy.
[0101] The test shows that the density of the prepared 90W-8Co-2Al tungsten alloy is 17.7g / cm 3 .
[0102] The microstructure of the prepared 90W-8Co-2Al tungsten alloy was observed, and it was found that the tungsten alloy was mainly composed of W phase and γ solid solution phase, and a small amount of L12 phase was precipitated in the γ solid solution phase.
[0103] Dynamic compression test was carried out on the prepared 90W-8Co-2Al tungsten alloy, and it was found that the tungsten alloy exhibited adiabatic shear failure.
[0104] Comparative Example 1
[0105] The specific steps of preparing 90W-5Co-5Al tungsten alloy by traditional liquid phase sintering process are as follows:
[0106] (1) After grinding, cleaning and drying pure metal blocks of Co and Al with a purity of not less than 99.7%, a mixed raw material with a total mass of 2000±0.01 g is weighed according to a mass ratio of Co:Al=5:5; the weighed mixed raw materials are placed in a water-cooled copper crucible of a vacuum gas atomization powder making furnace in the order of their melting points from low to high, and then the furnace is evacuated until the vacuum degree in the furnace reaches 3×10 -3 After the alloy is completely melted into alloy liquid, argon is used as an atomizing medium to atomize the alloy liquid at a heating power of 150kW and an atomizing pressure of 4MPa, and then a Co-Al pre-alloyed powder with a particle size of ≤38μm is obtained through vacuum screening equipment;
[0107] (2) spherical W powder with a particle size of no more than 15 μm and the Co-Al pre-alloyed powder prepared in step (1) are weighed in a mass ratio of 90:10 to obtain a mixed powder with a total mass of 1000±0.01 g, and the mixed powder is placed in a clean and blown-dried V-type powder mixer, mixed at a speed of 300 r / min for 24 h, and then placed in a vacuum drying oven at 130° C. for vacuum drying for 4 h to obtain a uniformly mixed and dry mixed powder;
[0108] (3) The mixed powder obtained in step (2) is placed in a Φ20 mm × 180 mm cold isostatic pressing mold and sealed tightly, and then placed in a cold isostatic press, pressurized to 100 MPa and maintained at a pressure of 120 min, taken out, cleaned, demolded to obtain a green compact; the green compact is placed in a crucible covered with alumina particles and placed in a box-type high-temperature sintering furnace, first heated to 850° C. at a heating rate of 30° C. / min and kept warm for 120 min, then heated to 1500° C. at a heating rate of 10° C. / min and kept warm for 16 h, and then cooled to obtain a sintered body;
[0109] (4) The sintered body was subjected to hot isostatic pressing at 900°C and 120 MPa for 10 h to obtain 90W-5Co-5Al tungsten alloy.
[0110] The test shows that the density of the prepared 90W-5Co-5Al tungsten alloy is 17.7g / cm 3 .
[0111] The microstructure of the prepared 90W-5Co-5Al tungsten alloy was observed, and it was found that the tungsten alloy was mainly composed of W phase and γ solid solution phase, and a large amount of L12 phase was precipitated in the γ solid solution phase.
[0112] The prepared 90W-5Co-5Al tungsten alloy was subjected to a dynamic compression test, and it was found that the tungsten alloy showed an upset morphology and no adiabatic shear fracture occurred.
[0113] Comparative Example 2
[0114] The specific steps of preparing 90W-4Co-0.5Al-3.5Ta-2Ti tungsten alloy by traditional liquid phase sintering process are as follows:
[0115] (1) After the pure metal blocks of Co, Al, Ta and Ti with a purity of not less than 99.7% are polished, cleaned and dried, a mixed raw material with a total mass of 2000±0.01g is weighed according to the mass ratio of Co:Al:Ta:Ti=40:5:35:20; the weighed mixed raw materials are placed in a water-cooled copper crucible of a vacuum gas atomization powder making furnace in the order of their melting points from low to high, and then the furnace is evacuated until the vacuum degree in the furnace reaches 3×10 -3 After the alloy is completely melted into alloy liquid, argon is used as an atomizing medium to atomize the alloy liquid at a heating power of 160 kW and an atomizing pressure of 4 MPa, and then a Co-Al-Ta-Ti pre-alloyed powder with a particle size of 38 to 150 μm is obtained through a vacuum screening device;
[0116] (2) spherical W powder with a particle size range of 15 to 25 μm and the Co-Al-Ta-Ti pre-alloyed powder prepared in step (1) are weighed in a mass ratio of 9:1 to obtain a mixed powder with a total mass of 1000±0.01 g, and the mixed powder is placed in a clean and blown-dried V-type powder mixer, mixed at a speed of 300 r / min for 24 h, and then placed in a vacuum drying oven at 130° C. for vacuum drying for 4 h to obtain a uniformly mixed and dry mixed powder;
[0117] (3) The mixed powder obtained in step (2) is placed in a cold isostatic pressing mold of Φ20 mm×180 mm and sealed, and then placed in a cold isostatic press, pressurized to 150 MPa and maintained at the pressure for 25 minutes, taken out, cleaned, demolded to obtain a pressed green body; the pressed green body is placed in a crucible covered with alumina particles and placed in a box-type high-temperature sintering furnace, first heated to 900°C at a heating rate of 20°C / min and kept warm for 120 minutes, then heated to 1600°C at a heating rate of 10°C / min and kept warm for 12 hours, and then cooled to obtain a sintered body;
[0118] (4) The sintered body was hot isostatically pressed at 900°C and 120 MPa for 10 h to obtain a 90W-4Co-0.5Al-3.5Ta-2Ti tungsten alloy.
[0119] The test shows that the density of the prepared 90W-4Co-0.5Al-3.5Ta-2Ti tungsten alloy is 17.2g / cm 3 .
[0120] Phase analysis of the prepared 90W-4Co-0.5Al-3.5Ta-2Ti tungsten alloy showed that the tungsten alloy was mainly composed of W phase and γ solid solution phase. A large amount of Co3W phase appeared in the alloy matrix, but no L12 phase was precipitated.
[0121] Since the tungsten alloy has very poor strength and plasticity, it is impossible to complete the quasi-static mechanical properties test and dynamic mechanical properties test.
[0122] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-density tungsten alloy with high adiabatic shear sensitivity and high strength and plasticity, characterized by: A tungsten alloy composed of W, Co, Al, M and N in the mass percentage of a:b:c:d:e, wherein the M element is at least one of Ni, Fe, V, Cr, Ta and Nb, and the N element is at least one of Y, V, Mo, Mn, Hf and Ti, 90%≤a≤95%, 1%≤b≤8%, 0.5%≤c≤4.5%, 0≤d≤3%, 0≤e≤3%, and d+e<b, a+b+c+d+e=100%, and the microstructure of the tungsten alloy includes W phase, γ solid solution phase and L12 phase; The preparation method of the high-density tungsten alloy specifically comprises the following steps: (1) uniformly mixing the single substance powders corresponding to each element, or uniformly mixing the W single substance powder and the CoAlMN alloy powder to obtain a mixed powder; (2) liquid-phase sintering the mixed powder to obtain a sintered body; (3) The sintered body is subjected to annealing or hot isostatic pressing to obtain the tungsten alloy.
2. A high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity according to claim 1, characterized in that: The M element is at least one of Ni, Fe, and Ta, and the N element is one or both of Hf and Ti.
3. A high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity according to claim 1 or 2, characterized in that: 90%≤a≤95%, 3%≤b≤7%, 0.5%≤c≤3%, 0≤d≤2.5%, 0≤e≤2.5%, and d+e<b, a+b+c+d+e=100%.
4. A method for preparing a high-density tungsten alloy having high adiabatic shear sensitivity and high strength plasticity as claimed in any one of claims 1 to 3, characterized in that: The specific steps include: (1) uniformly mixing the single substance powders corresponding to each element, or uniformly mixing the W single substance powder and the CoAlMN alloy powder to obtain a mixed powder; (2) liquid-phase sintering the mixed powder to obtain a sintered body; (3) The sintered body is subjected to annealing or hot isostatic pressing to obtain the tungsten alloy.
5. The method for preparing a high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity according to claim 4, characterized in that: In step (1), after weighing each raw material powder, uniformly mix them at a speed of 30 to 600 r / min for 4 to 24 hours under an inert gas protective atmosphere, and then place them in a vacuum drying oven at 100 to 180° C. for vacuum drying for 2 to 8 hours to obtain a mixed powder.
6. The method for preparing a high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity according to claim 4, characterized in that: In step (2), a conventional liquid phase sintering process is used to prepare a sintered body, and the specific process conditions are as follows: a box-type high-temperature sintering furnace is selected, and the temperature is first increased to 700-1000°C at a heating rate of 5-20°C / min and kept at this temperature for 60-120min, and then the temperature is increased to 1300-1700°C at a heating rate of 2-20°C / min and kept at this temperature for 0-120h, and a sintered body is obtained after cooling.
7. The method for preparing a high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity according to claim 4, characterized in that: In step (2), a laser transient liquid phase sintering process is used to prepare a sintered body, and the specific process conditions are as follows: laser power 800-2000 W, scanning rate 300-1500 mm / min, powder feeding rate 15-45 g / min, scanning spacing 1.0-3.0 mm, and elevation 0.1-0.5 mm.
8. The method for preparing a high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity according to claim 4, characterized in that: In step (3), the annealing temperature of the annealing treatment is 500-1100° C. and the annealing time is 2-24 hours.
9. The method for preparing a high-density tungsten alloy with high adiabatic shear sensitivity and high strength plasticity according to claim 4, characterized in that: In step (3), the temperature of the hot isostatic pressing treatment is 800-1500° C., the pressure is 80-230 MPa and the time is 2-24 hours.
Citation Information
Patent Citations
Stripped tungsten alloy material with self-sharpening structure, as well as preparation method and application thereof
CN111283212A
Method for improving adiabatic shear sensitivity of pure tungsten metal through crystal texture design
CN115007645A
High-strength tungsten-based alloy and preparation method thereof
CN109778042A
Energetic tungsten alloy material and preparation method thereof
CN114657431A
Preparation method of superfine tungsten alloy material
CN115505772A